A Soybean Oil-Based Liposome-Polymer Transfection Complex as a Codelivery System for DNA and Subunit Vaccines. (15th February 2012) - Lin, Yu-Ling; Chen, Li-Yi; Chen, Chia-Hung; Liu, Yen-Ku; Hsu, Wei-Tung; Ho, Li-Ping; Liao, Kuang-Wen
Abstract : Inexpensive liposome-polymer transfection complexes (LPTCs) were developed and used as for DNA or protein delivery. The particle sizes of the LPTCs were in the range of 212.2 to 312.1 nm, and the zetapotential was +38.7 mV. LPTCs condensed DNA and protected DNA from DNase I digestion and efficiently delivered LPTC/DNA complexes in Balb/3T3 cells. LPTCs also enhanced the cellular uptake of antigen in mouse macrophage cells and stimulated TNF-α release in naïve mice splenocytes, both indicating the potential of LPTCs as adjuvants for vaccines. In vivo studies were performed using H. pylori relative heat shock protein 60 as an antigen model. The vaccination of BALB/c mice with LPTC-complexed DNA and protein enhanced the humoral immune response. Therefore, we developed a DNA and protein delivery system using LPTCs that is inexpensive, and we successfully applied it to the development of a DNA and subunit vaccine.